The effect of active and passive smoking during pregnancy on birth outcomes: A cohort study in Shanghai - Xiaokai Wang; Xia Gao; De Chen; Xuelian Chen; Qingwei Li; Jiani Ding; Fangyuan Yu; Xiaoyun Zhu; Nannan Zhang; Yifang Chen (Tobacco Induced Diseases)
Introduction China is the largest tobacco consumer in the world, and tobacco poses a serious threat to the health of pregnant women. However, there are relatively few domestic studies on smoking during pregnancy and childbirth outcomes among pregnant women. The purpose of this study was to analyze the effect of active and passive smoking on pregnant women and their pregnancy outcomes, providing evidence and recommendations for intervention measures.